Garçons manqués and femmes fortes: Two ambivalent figures of butch lesbianism in women's football in Cameroon - Ndjio, Basile (African Studies Review, 2022)
With the enactment of anti-homosexuality laws in the 1960s, Cameroon's government officially endorsed heterosexualist ideologies which legitimize the alienation and criminalization of minority and nonconforming sexual and gender identities. One group, the so-called garçons manqués, embodies the stigmatized masculine or "butch" lesbian identity. The political management of lesbianism in Cameroon is ambivalent, however, with respect to sport, and particularly regarding the national pastime, football. Whereas masculine lesbians are routinely branded as "butches" or "sexual predators" who threaten African hetero-patriarchy, "strong women"" (femmes fortes) are celebrated as pivotal to the national ambition. Cameroon's government strategically amalgamates both heteronationalism and homonationalism in the interest of national pride.
Keywords: afrique; anthropologie; approches et analyses; butch; cameroun; discipline; discours dominant; hétérosexisme; personnes lesbiennes; ressource en ligne; régions géographiques; sciences humaines; sexisme; sport; systèmes d'oppressions

Don’t give mum chocolates for Mother’s Day. Take on more housework, share the mental load and advocate for equality instead - Ruppanner, Léa (The Conversation, 2022)
Keywords: 2000 à aujourd'hui; approches et analyses; care; charge mentale; charge émotionnelle; discipline; hétérosexisme; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible

Discours sur le corps et la sexualité des femmes : analyse de la réception médiatique du mouvement Femen - Tremblay, Stéphanie (Université du Québec à Montréal, 2022)
Le mouvement Femen est un groupe féministe international qui manifeste seins nus. Au Québec comme un peu partout dans le monde, les Femen attirent l’attention des médias. Le discours médiatique entourant ce mouvement constitue donc un objet d’étude intéressant afin d’explorer la question plus large du rapport au corps et à la sexualité des femmes. Dans le cadre de ce projet, une analyse critique de discours a été menée sur 214 textes issus de cinq groupes de quotidiens québécois francophones. Alors qu’on tend à penser que l’égalité entre les sexes est atteinte au Québec, le discours médiatique québécois entourant le mouvement Femen révèle que le corps, la nudité et la sexualité des femmes font l’objet d’un contrôle social en plus d’un regard patriarcal, colonialiste et hétéronormé. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Femen, agentivité sexuelle, slut-shaming, discours médiatique, féminisme, corps, nudité
Keywords: 2000 à aujourd'hui; 2010-2019; agentivité sexuelle; amériques; analyse de discours; approches et analyses; corps; discipline; hétérosexisme; intersectionnalité; militance; mémoires/thèses; nudité; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; système colonial; systèmes d'oppressions; thématiques; violences